Exciton delocalization length in chlorosomes investigated by lineshape dynamics of two-dimensional electronic spectra. Issue 42 (9th September 2021) - Jun, Sunhong; Yang, Cheolhee; Choi, Seungjoo; Isaji, Megumi; Tamiaki, Hitoshi; Ihee, Hyotcherl; Kim, Jeongho
Abstract : The spectral and temporal profiles of exciton delocalization length in chlorosomes are determined with two-dimensional electronic spectroscopy. Abstract : A chlorosome, a photosynthetic light-harvesting complex found in green sulfur bacteria, is an aggregate of self-assembled pigments and is optimized for efficient light harvesting and energy transfer under dim-light conditions. In this highly-disordered aggregate, the absorption and transfer of photoexcitation energy are governed by the degree of disorder. To describe the disorder, the number of molecules forming excitons, which is termed exciton delocalization length (EDL), is a relevant parameter because the EDL sensitively changes with the disorder of the constituent molecules. In this work, we determined the EDL in chlorosomes using two-dimensional electronic spectroscopy (2D-ES). Since spectral features correlated with EDL are spread out in the two-dimensional (2D) electronic spectra, we were able to determine the EDL accurately without the effects of homogeneous and inhomogeneous line broadening. In particular, by taking advantage of the multi-dimensionality and the time evolution of 2D spectra, we not only determined the excitation frequency dependence of EDL but also monitored the temporal change of EDL. We found that the EDL is ∼7 at 77 K and ∼6 at 298 K and increases with the excitation frequency, with the maximum located well above the maximum of the absorption spectrum of chlorosomes. The spectral profile of EDL changes rapidly within 100 fs and becomes flat over time due to dephasing of initial exciton coherence. From the coherent oscillations superimposed on the decay of EDL, it was learned that high-frequency phonons are more activated at 298 K than at 77 K.